KUALITAS BIJI DAN KARAKTER AGRONOMI PADI HITAM (Oryza sativa L.) LOKAL PEKALONGAN DENGAN PENAMBAHAN PAKLOBUTRAZOL DAN GIBERELIN - Endang Triyani Prihantari; Triani Hardiyati; Siti Samiyarsih (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Black rice (Oryza sativa L.) is a rice variety that has many additional functions and is used as a functional food. However, black rice has a longer harvest period and has a higher apparent stem height than other types of rice so that black rice plants are easy to break. This will reduce the quality of rice plants. One of the methods that can be done to overcome this problem is treating by paclobutrazol and gibberellin. The combination of paclobutrazol and gibberellin is expected to provide better rice growth and improve the quality of rice seeds. The purpose of this study was to determine the effect of the addition of paclobutrazol and gibberellin on seed quality, palea-lemma size and agronomic character of local Pekalongan black rice (Oryza sativa L.). The research was conducted experimentally using a completely randomized design (CRD) of factorial treatment pattern. The first factor was paclobutrazol with 4 levels of concentration (0 ppm, 100 ppm, 200 ppm and 300 ppm) applied once at 4 weeks of plant age and the second factor was gibberellin with 4 levels of concentration (0 ppm, 100 ppm, 200 ppm and 300 ppm ) applied once at the age of 6 weeks of plants, so that are 48 combinations with each treatment was replicated 3 times. The parameters observed included plant height, leaf width, flowering age, harvest age, palea-lemma size, weight of 100 seeds, protein and amylose content. The data obtained were analyzed using the ANOVA test at the 95% confidence level, and continued with the Honestly Significant Difference (HSD) test at an error rate of 5%.The results showed that the interaction between paclobutrazol and gibberellin was not significant, but treatment of 300 ppm paklobutrazol showed the best results in plant height inhibition, while the treatment of paclobutrazol 200 ppm was the best concentration to stimulate flowering and harvesting age. Treatment of gibberellin 100 ppm was found the best concentration to increase leaf width while a concentration of 300 ppm proved to give the best results for palea-lemma size, amylose content, protein content and weight of 100 seeds per plant.